Rehabilitation in oncology. - Fernandes, M S; Jordão, J M (Acta Médica Portuguesa, 1989)
The A.A. emphasize the importance of Physical Medicine and Rehabilitation in oncologic treatment. The most significant aspects of psychiatric therapy were analyzed in a special group on oncologic diseases, such as breast cancer, malignant tumors of the limb bones and in the inactivity-desuse syndrome. It is concluded that rehabilitation treatment could be generalized to a larger group of oncologic situations.